Human Physiology During Exposure to the Cave Environment: A Systematic Review With Implications for Aerospace Medicine - Zuccarelli, Lucrezia; Galasso, Letizia; Turner, Rachel; Coffey, Emily J. B.; Bessone, Loredana; Strapazzon, Giacomo (Frontiers in Physiology, 2019)
Background: Successful long-duration missions outside low-Earth orbit will depend on technical and physiological challenges under abnormal environmental conditions. Caves, characterized by absence of light, confinement, three-dimensional human movement and long-duration isolation, are identifiably one of the earliest examples of scientific enquiry into space analogues. However, little is known about the holistic human physiological response during cave exploration or prolonged habitation. The aim of our review was to conduct a systematic bibliographic research review of effects of short and prolonged exposure to cave environment on human physiology, with a view to extend the results to implications for human planetary exploration missions. Methods: A systematic search was conducted following the structured PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for electronic databases. Results: The search retrieved 1519 studies. There were 50 articles selected for further revision, of which 31 met our inclusion criteria. Cardiovascular, endocrine-metabolic, immunologic-haematological, muscular responses and visual dysfunction were investigated in short-term exposure cave studies. Prolonged exposure studies mainly investigated whether biological rhythms persist or desist in the absence of standard environmental conditions. Studies have shown a reasonable interference based on specific subterranean protocols already with short exposure. During underground cave isolation changes in circadian system frequency are demonstrated. Conclusions: This review facilitates further comparison with knowledge in related disciplines pertaining to human preparation in challenging environments, stimulates research, and offers an opportunity to utilise this overview to inform advanced study design and noteworthy research focus in future human space analogue research in subterranean environments.